STRATEGY CREATING POSITIVE WORD OF MOUTH BASED ON RELATIONSHIP QUALITY - Firdaus, Firdaus; Mulyanto, Kukuh (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2020)
The development of technology had a great impact on the company in introducing or marketing their products to consumers, marketing has become the world's interest. They market of goods, services, property, people, places, events, information, ideas, and organizations. In order to maintain its position in the eyes of consumers, marketers strive to create an ideas and innovation that can attract the interest of market participants. The purpose of this research is done in order to examine the information of variable quality, assurance and responsiveness to the quality of relationships that affect consumer promotions lazada mouth to mouth in Semarang. This data research using questionnaires with a sample of 148 respondents in the city of Semarang. The sampling technique is to use probability sampling, with one of the methods used is purposive sampling. The data obtained and analyzed by Structural Equation Modeling (SEM) with AMOS application 21. The results of this study are: (1) the quality of information, assurance and responsiveness positive and significant impact on the quality of the relationship. (2) the quality of information, assurance, responsiveness and quality of the relationship positive and significant effect on word of mouth.